Multi Agent Systems based CPPS – An Industry 4.0 Test Case - Bendjellou, Abdelhamid; Gaham, Mehdi; Bouzouia, Brahim; Moufid, Mansour; Mihoubi, Bachir (University of Eloued جامعة الوادي, 2022)
With the rise of the Industry 4.0 Revolution, Artificial Intelligence, digitalization, and connectivity have been more than ever; adopted in the industrial world. This adoption is leading to the transformation of the mechatronic systems used in production into Cyber-Physical Production Systems. Such a concept is taking industrial Automation and computer integrated manufacturing to the next level. The massive migration of traditional production systems into Cyber-Physical Production Systems, including the MAS-based CPPS, made the reviewing of the traditional methods of Engineering and Commissioning a must. Which explains the increase in the number of research works during recent years about the application of these Architectures on practical cases. In the present paper, we propose a way of developing and implementing MAS-based CPPS on an Industry 4.0 Assembly Platform. Moreover, we test the behavior of the Multi-Agent systems with interaction with SIEMENS Programmable Logic Controllers via OPC UA Protocol, during a Software-In-the-Loop “SIL” Test on a 3D Model of the Platform running on a separate Computer. The test assesses the behavior of the components of a typical Cyber-Physical production module during the treatment of a given operation on the product, to extract the vulnerabilities in the treatment of the operation and search for appropriate improvements.
Forum Intervention of Artificial Intelligence and Its Applications. Faculty of Exat science. University of Eloued
Keywords: Multi Agent Systems, Cyber Physical Production Systems, Intelligent Manufacturing Systems, SIL-Testing